2016
DOI: 10.1007/s00232-016-9877-2
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity of Japanese Quince Extract and Its Interactions with Lipids, Erythrocyte Membrane, and Human Albumin

Abstract: The aim of the study was to determine in vitro biological activity of fruit ethanol extract from Chaenomeles speciosa (Sweet) Nakai (Japanese quince, JQ) and its important constituents (−)-epicatechin (EC) and chlorogenic acid (CA). The study also investigated the structural changes in phosphatidylcholine (PC) liposomes, dipalmitoylphosphatidylcholine liposomes, and erythrocyte membranes (RBC) induced by the extract. It was found that the extract effectively inhibits oxidation of RBC, induced by 2,2′-azobis (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 66 publications
5
33
0
1
Order By: Relevance
“…These results well correlate with our previously published data, that the Stern-Volmer constant for the chlorogenic acid -human serum albumin association is 3.0 × 10 4 M -1 . In addition, the calculated values of the bimolecular quenching rate constant (K Q ) is 6.04 × 10 12 M -1 s indicates at the static mechanism of quenching [18]. …”
Section: Fluorescence Quenching Mechanism and Determination Of Bindinmentioning
confidence: 86%
See 4 more Smart Citations
“…These results well correlate with our previously published data, that the Stern-Volmer constant for the chlorogenic acid -human serum albumin association is 3.0 × 10 4 M -1 . In addition, the calculated values of the bimolecular quenching rate constant (K Q ) is 6.04 × 10 12 M -1 s indicates at the static mechanism of quenching [18]. …”
Section: Fluorescence Quenching Mechanism and Determination Of Bindinmentioning
confidence: 86%
“…Such a high activity may result from favorable molecular structure of the Q components, which include phenolic acid but also flavonols and flavan-3-ols [28]. Our previous results [18] showed that the main component of the extract of quincechlorogenic acid has about 3.3 and 7.7 (for PC membrane and RBC, respectively) times greater activity than quince extract (Table 2). It can be assumed that the antioxidant activity of the extract is related to the high content of chlorogenic acid, which has a high antioxidant capacity.…”
Section: Antioxidant Activitymentioning
confidence: 88%
See 3 more Smart Citations